DEVELOPING EMPATHY ABILITY BY STORY-TELLING WITH PUPPET FOR EARLY CHILDHOOD STUDENT IN LENTERA ALAM LEARNING CENTER - Beatriks Novianti Kiing-Bunga; Indra Yohanes Kiling (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2016)
The root of empathy has been planted in person since he/she was a baby. Then one of the way to despite foundation of moral education and built children empathy has to be done since early life. Empathy is an ability to understand others’ feeling and capability to put self on others condition. This research used Action Research Method and aims to know children’s empathy after they performs a folklore story by using puppet in front of their friends. This research engaged 5 students aged 5 years old in Lentera Alam Learning Center. There were four steps, 1) Planning; 2) Action; 3) Observation; and 4) Reflection which were done in two cycles. The treatment was teacher told a folklore story to children, then ask children to retell the story for his/her friend by using puppets in front of the class. Check list observation was used during the performance on the first and second cycle. It was found an improvement on children’s empathy, before the treatment pre-test score is 11.2 then post-test on the first cycle 16.8 and the second cycle 22.4. Children’s empathy shown by the ability to distinguished emotions, sharing, helping, asking apologize, giving forgiveness and cheering others friend when they were sad.